Understanding microblogging hashtags for learning enhancement - Malinka Ivanova (Firenze University Press, 2013)
The use of hashtags in Twitter messages is growing among the educational community for various reasons. Exploring and understanding how hashtags can facilitate learning and self-learning organization is the main aim of this paper. Several online available tools for hashtags management are examined and their recognition and utilization can assist knowledge gathering and learning network constructing.